2010
DOI: 10.1161/atvbaha.110.209783
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Is an Endogenous Inhibitor of Phosphodiesterase Activity

Abstract: Objective-Recent studies have demonstrated that hydrogen sulfide (H 2 S) is produced within the vessel wall from L-cysteine regulating several aspects of vascular homeostasis. H 2 S generated from cystathione ␥-lyase (CSE) contributes to vascular tone; however, the molecular mechanisms underlying the vasorelaxing effects of H 2 S are still under investigation. Methods and Results-Using isolated aortic rings, we observed that addition of L-cysteine led to a concentrationdependent relaxation that was prevented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
246
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 315 publications
(258 citation statements)
references
References 26 publications
5
246
1
6
Order By: Relevance
“…We also investigated several previously defined targets of H 2 S in other systems, including K ϩ ATP channels, cGMP-dependent phosphodiesterases (51), and Akt (52) and found that these are not responsible for the effects of H 2 S on T cell activation (supplemental Fig. 1).…”
Section: Journal Of Biological Chemistry 4215mentioning
confidence: 97%
“…We also investigated several previously defined targets of H 2 S in other systems, including K ϩ ATP channels, cGMP-dependent phosphodiesterases (51), and Akt (52) and found that these are not responsible for the effects of H 2 S on T cell activation (supplemental Fig. 1).…”
Section: Journal Of Biological Chemistry 4215mentioning
confidence: 97%
“…CBS and CSE are differentially expressed in cardiovascular as well as in several other body districts (13). The physiological functions of H 2 S are mediated by a variety of molecular targets, including ion channels and signaling proteins (16)(17)(18). Alterations in H 2 S metabolism contribute to an array of cardiovascular disorders such as hypertension, atherosclerosis, heart failure, and diabetes (19).…”
mentioning
confidence: 99%
“…H 2 S has been shown to dilate other isolated mammalian blood conduits in vitro, such as human internal mammary artery [103], mouse aorta and ear microcirculation [104,105], and newborn pig cerebral arterioles [106]. Consistent with these data, the systemic injection of NaHS at 10-50 activity in VSMCs, which leads to vasorelaxation in a PKG-dependent manner [48,111,112]. In primariy aortic ECs isolated from WT mice, H 2 S activates the PI-3K/Akt signaling pathway following increased eNOS phosphorylation in Ser-1177, thereby increasing NO production [47].…”
Section: The Roles Of H 2 S and No In Vasodilationmentioning
confidence: 69%